Evaluasi Pada Variasi Proses Bisnis Layanan Donor Darah (Studi Kasus : UTD PMI Kota Malang) - Inggrid E. A. Siahaan; Nanang Yudi Setiawan; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PMI Malang has an unit called Unit Transfusi Darah (UTD). UTD PMI Malang is a health services facility with primary activities, that are blood donor service, blood supply, and blood distribution. In doing its primary activities, UTD PMI Malang cannot be separated with its support activities which support all of the primary. These primary and support activities are clasified using value chain analysis method to get activities that directly affect and connect effectively to optimize its service performance. Based on the observation, UTD PMI Malang has variations of service in every process. These variations of service are identified and evaluated for impact and its relation to the performance of service. Through the interview process, obtained 11 business processes that have relevance with variation of service in UTD PMI Malang, which is further modeled with Business Process Model and Notation (BPMN). Modelling helps to see appearance of process variation, that make easier to determine the type of variability, wether included in variability by extention or by restriction. Then, these business process are evaluated with Quality Evaluation Framework (QEF), which results in 4 quality factors that having incompatibility between the target and its quality. Three of them affect the appearance of variation in provided service. These variation appear as variability by extension.